Phonological representations in children wih SLI - Claessen, Mary; Leitao, Suze (Sage Publications, 2012)
It has been hypothesized that children with specific language impairment (SLI) have difficulty processing sound-based information, including storing and accessing phonological representations in the lexicon. Tasks are emerging in the literature that provide a measure of the quality of stored phonological representations, without requiring a verbal response. This article describes the performance of children with specific language impairment (SLI) (n = 21), typically developing children matched for age (n = 21), and typically developing children matched for language (n = 21) on two measures of phonological representations – the Quality of Phonological Representations (QPR) and the Silent Deletion of Phonemes (SDOP) – and a measure of phonological awareness, the Sutherland Phonological Awareness Test: Revised (SPAT-R). As predicted the age-matched (AM) group demonstrated significantly better performance on all tasks than the SLI group. The AM group performed significantly better than the language-matched (LM) group on the SDOP and SPAT tasks, but not significantly differently on the QPR task. The SLI group performed significantly better than the LM group on both the SDOP and SPAT, but their performance on the QPR was significantly weaker than the LM group. The findings of this study provide support for the notion of lower quality phonological representations in children with SLI thus placing them at increased risk of ongoing language and literacy difficulties.